Use of Konjac Powder in Mulberry Jelly Gummy Products - Onsamlee, Gannigar; Srikok, Sirilada (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2022)
This research aimed to study effect of konjac powder in mulberry jelly gummy products. The chemical quality of mulberry juice, the optimum amounts of mulberry juice and konjac powder in mulberry jelly gummy products, were evaluated. The results showed that the optimum amounts of mulberry juice and konjac powder were 75 g and 3 %, respectively, of the total ingredients. Mulberry jelly gummy products fortified with konjac powder consisted of mulberry juice, sugar, gelatin, glucose syrup, konjac powder, citric acid at 41.61 %, 41.50 %, 9.17 %, 3.49 %, 2.91 % and 1.32 %, respectively. The chemical properties consisted of moisture, carbohydrates, proteins, fats, fibers, ash at 18.75 %, 71.89 %, 6.88 %, 0.30 %, 1.65 % and 0.53 % respectively, and total calories were 317.78 kcal/100 g. The total titratable acidity of citric acid was 0.11 % with the pH of 2.97. The physical properties including hardness (N), adhesiveness, springiness, cohesiveness, gumminess, chewiness were 277.38 N, -187.23, 0.86, 0.81, 197.64 and 277.76, respectively. The amount of total soluble solids was 21.03 °brix and water activity (aw) was 0.76. The final product in terms of microorganism properties was within the Thai community product standard at 520/2547.The consumers accepted the product at the level of like very much (8.24 scores).